-57x=-7

Multiply both sides of the equation by -75.

-75⋅(-57)⋅x=-75⋅-7

Simplify -75⋅(-57)⋅x.

Cancel the common factor of 7.

Move the leading negative in -75 into the numerator.

-75⋅(-57)⋅x=-75⋅-7

Move the leading negative in -57 into the numerator.

-75⋅-57⋅x=-75⋅-7

Factor 7 out of -7.

7(-1)5⋅-57⋅x=-75⋅-7

Cancel the common factor.

7⋅-15⋅-57⋅x=-75⋅-7

Rewrite the expression.

-15⋅-5⋅x=-75⋅-7

-15⋅-5⋅x=-75⋅-7

Cancel the common factor of 5.

Factor 5 out of -5.

-15⋅(5(-1))⋅x=-75⋅-7

Cancel the common factor.

-15⋅(5⋅-1)⋅x=-75⋅-7

Rewrite the expression.

-1⋅-1⋅x=-75⋅-7

-1⋅-1⋅x=-75⋅-7

Multiply.

Multiply -1 by -1.

1⋅x=-75⋅-7

Multiply x by 1.

x=-75⋅-7

x=-75⋅-7

x=-75⋅-7

Multiply -75⋅-7.

Multiply -7 by -1.

x=7(75)

Combine 7 and 75.

x=7⋅75

Multiply 7 by 7.

x=495

x=495

x=495

The result can be shown in multiple forms.

Exact Form:

x=495

Decimal Form:

x=9.8

Mixed Number Form:

x=945

Solve for x -5/7x=-7